DA'WAH STRATEGY THROUGH THE BOOK OF 'AQIDATUL MUJMALAH' AT THE MAJELIS TAKLIM KH. ABDULLAH SHAFI'I: Analysis of Methods and Their Impact On Strengthening Aqidah - Anim, Sarbini; Uyuni, Badrah; Majid, Zamakhsyari Abdul (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2024)
This article examines the da'wah strategy applied by KH. Abdullah Syafi'i, through the teaching of the book Aqidatul Mujmalah in his majelis taklim, focused on teaching methods, socio-religious impacts, and their relevance in the context of contemporary da'wah. This research uses a qualitative approach with a case study method involving participatory observation, in-depth interviews with Ustaz and worshippers, and documentation analysis in the form of teaching recordings and related materials. The results of the study revealed that KH. Abdullah Shafi'i combines teaching classical books with the practice of dhikr and dialogical-interactive methods, creating a da'wah approach that strengthens not only the intellectual but also spiritual aspects of the congregation. The impact can be seen in three main aspects: increasing the understanding of the faith, strengthening faith through internalizing monotheistic values, and community social development through religious and social activities. The relevance of this da'wah strategy is increasingly seen in modern da'wah, where adaptation to digital technology and social media is the key to expanding the reach of Islamic teachings. This article makes theoretical and practical contributions to developing a contextual, adaptive, and effective model of Islamic da'wah. It offers insights for scholars and academics to combine classical traditions with modern innovations in spreading Islamic values. This study recommends a follow-up study on adapting classical da'wah methods to face the challenges of globalization and modernization.